Pengaruh Pemanfaatan Media Online Terhadap Minat Berwirausaha pada Mahasiswa (Studi Kasus di Sekolah Tinggi Multi Media “MMTC” Yogyakarta) - Dhety Chusumastuti (Jurnal Riset Inspirasi Manajemen dan Kewirausahaan, 2020)
This study aims to determine the effect of Online Media Utilization on Entrepreneurial Interest in Students at STMM Yogyakarta. The sample in this study were 94 students at STMM Yogyakarta. Data was collected by survey method by giving a list of questions or questionnaires directly to the respondents. Data analysis techniques in this study used Simple Regression analysis, and t test which was operated through the SPSS program. The results showed that the use of online media had a positive and significant influence on entrepreneurial interest in students at STMM Yogyakarta.